Investigating the influence of firm characteristics on the ability to exercise market power: A stochastic frontier analysis approach with an application to the iron ore market - Robert Germeshausen; Timo Panke; Heike Wetzel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper empirically analyzes the existence of market power in the global iron ore market during the period 1993-2012 using an innovative Stochastic Frontier Analysis approach introduced by Kumbhakar et al. (2012). In contrast to traditional econometric procedures, this approach allows for the estimation of firm- and time-specific Lerner indices and, therefore, the assessment of the influence of individual firm characteristics on the ability to generate markups. We find that markups on average amount to 20%. Moreover, location and experience are identified to be the most important determinants of the magnitude of firm-specific markups.
urn:nbn:de:bsz:180-madoc-374237
Keywords: D22; L11; L72; 330; Estimation of market power; Lerner indices; Stochastic Frontier Analysis; Non-renewable resources